Sinergitas Guru Pendidikan Agama Kristen dan Guru Bimbingan Konseling Dalam Konseling Pastoral Kepada Siswa Dari Keluarga Broken Home Di Smk PP Negeri Kalasey - Sipahutar, Elizabeth Nastasya; Weol, Wolter; Brek, Yohan (DELAHA: Journal of Theological Sciences, 2024)
This article aims to identify and analyze the synergy of Christian Religious Education teachers and Counseling Guidance teachers in pastoral counseling to students from broken home families at SMK PP Negeri Kalasey. This study used an analytic descriptive qualitative research approach. Data were collected through observation, interviews and documentation. From the results of data analysis and interpretation, it is obtained that Christian Religious Education teachers in teaching and providing counseling guidance to students from broken home families synergize with Counseling Guidance teachers whose role is to provide counseling guidance to these students. This is indicated by the role of Christian Religious Education teachers and Counseling Guidance teachers collaborating to conduct pastoral counseling to students from broken home families and how Christian Religious Education teachers and Counseling Guidance teachers work together to conduct pastoral counseling. So from the findings it is recommended that all parties can work together in educating and guiding students from broken home families who have problems experiencing spiritual growth and better character changes.